Turismo e desenvolvimento - Ramirez, Lucas (Universidad Nacional del Litoral, 2020)
The town of Villa Elisa (province of Entre Ríos, Argentina) went through a deep and accelerated process of socioterritorial transformation motorized by the tourist-recreational use of the thermal water resource, which was concretized specifically with the construction and commissioning of a thermal complex (inaugurated to late 1999). This complex constituted the “core” from which the tourist dynamics of the place was configured - which also functionally involves the urban plant of the town - generating a specific form of territorial and economic organization; whose characterization and understanding forms the analytical object of this work. From a descriptive and exploratory methodological strategy, the tourist territory of the place is described; also identifying and understanding the role of the Municipality, of local social actors and economic agents for the management of the thermal resource, the provision of tourist services and the resulting urban transformations. Thus, the work allows us to review certain ideas about the term economic-territorial enclave, also reflecting on the notion and scope of “the local” as an analytical scale that allows not only to understand a case but also to interpret it in the light of the mentioned concept.